Utilization of healthcare services among Chinese migrants in Kenya: a qualitative study - Jialing Qiu; Duo Song; Juan Nie; Mengyi Su; Chun Hao; Jing Gu; Yuantao Hao; James N. Kiarie; Michael H. Chung (BMC, 2019)
Abstract Background The number of Chinese migrants in Sub-Saharan Africa (SSA) is increasing, which is part of the south-south migration. The healthcare seeking challenges for Chinese migrants in Africa are different from local people and other global migrants. The aim of this study is to explore utilization of local health services and barriers to health services access among Chinese migrants in Kenya. Methods Thirteen in-depth interviews (IDIs) and six focus group discussions (FGDs) were conducted among Chinese migrants (n = 32) and healthcare-related stakeholders (n = 3) in Nairobi and Kisumu, Kenya. Data was collected, transcribed, translated, and analyzed for themes. Results Chinese migrants in Kenya preferred self-treatment by taking medicines from China. When ailments did not improve, they then sought care at clinics providing Traditional Chinese Medicine (TCM) or received treatment at Kenyan private healthcare facilities. Returning to China for care was also an option depending on the perceived severity of disease. The main supply-side barriers to local healthcare utilization by Chinese migrants were language and lack of health insurance. The main demand-side barriers included ignorance of available healthcare services and distrust of local medical care. Conclusions Providing information on quality healthcare services in Kenya, which includes Chinese language translation assistance, may improve utilization of local healthcare facilities by Chinese migrants in the country.